Probiotics in food : health and nutritional properties and guidelines for evaluation : Report of a Joint FAO/WHO Expert Consultation on Evaluation of Health and Nutritional Properties of Probiotics in Food including Powder Milk with Live Lactic Acid Bacteria, Cordoba, Argentina, 1-4 October 2001 [and] Report of a Joint FAO/WHO Working Group on Drafting Guidelines for the Evaluation of Probiotics in Food, London, Ontario, Canada, 30 April -1 May 2002. - Food and Agriculture Organization of the United Nations; World Health Organization; Joint FAO/WHO Expert Consultation on Evaluation of Health and Nutritional Properties of Probiotics in Food including Powder Milk with Live Lactic Acid Bacteria; Joint FAO/WHO Working Group on Drafting Guidelines for the Evaluation of Probiotics in Food. (Rome [Italy] : Food and Agriculture Organization of the United Nations, World Health Organization, 2006)
"The beneficial effects of probiotic foods on human health and nutrition are increasingly recognized by health professionals. ... FAO and WHO initiated work to examine the scientific evidence on the functional and safety aspects of probiotics in food"--Foreword.
Includes bibliographical references.
Keywords: Gastrointestinal system -- Microbiology; Bacteria -- Health aspects; Microorganisms -- Therapeutic use; Food additives -- Health aspects; Probiotics; Health properties